Caspase-cleaved cytokeratin-18 and tumour regression in gastro-oesophageal adenocarcinomas treated with neoadjuvant chemotherapy - Fareed, Khaleel R.; Soomro, Irshad N.; Hameed, Khalid; Arora, Arvind; Lobo, Dileep N.; Parsons, Simon L.; Madhusudan, Srinivasan (Baishideng Publishing Group, 2012)
AIM: To examine cytokeratin-18 (CK-18) and caspase-cleaved CK-18 expression in tumours and correlate with clinicopathological outcomes including tumour regression grade (TRG) response.